2019 Joint Urban Remote Sensing Event (JURSE) 2019
DOI: 10.1109/jurse.2019.8808945
|View full text |Cite
|
Sign up to set email alerts
|

Rasterization strategies for airborne LiDAR classification using attribute profiles

Abstract: This paper evaluates rasterization strategies and the benefit of hierarchical representations, in particular attribute profiles, to classify urban scenes issued from multispectral LiDAR acquisitions. In recent years it has been found that rasterized LiDAR provides a reliable source of information on its own or for fusion with multispectral/hyperspectral imagery. However previous works using attribute profiles on LiDAR rely on elevation data only. Our approach focuses on several LiDAR features rasterized with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Among future works, we would like to see if combining the different features in a same network leads to better results. Indeed, it is a promising direction given our preliminary results with non-deep learning techniques [3]. Furthermore, we plan to investigate deep architectures among those well-established for semantic segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among future works, we would like to see if combining the different features in a same network leads to better results. Indeed, it is a promising direction given our preliminary results with non-deep learning techniques [3]. Furthermore, we plan to investigate deep architectures among those well-established for semantic segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study [3], we have shown that such alternative LiDAR rasterizations actually provide additional information source that can help to describe the contents of a remotely-sensed scene, and improve its classification. This was demonstrated using well-established multilevel features (attribute profiles) and classifier (RF).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual approach remains to first rasterize the point cloud to obtain a digital image (also called a raster of pixels) on which standard morphological operators are applied [18]. This strategy was also recently followed for morphological hierarchies on LiDAR point clouds [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example authors of [1] perform the segmentation and classification of urban point clouds with mathematical morphology after a projection of raw data on digital elevation model (DEM), and then re-project the results on point clouds. The same idea is used in [2] where a series of attribute profiles are computed on 2D grids containing various information related extracted during the mapping from 3D to 2D (number of points in a cell, first echo, last echo, . .…”
Section: Introductionmentioning
confidence: 99%